2005
DOI: 10.1177/021849230501300106
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dysfunction after Closure of Large Patent Ductus Arteriosus

Abstract: Changes in left ventricular dimensions and performance were studied in 43 patients after transcatheter occlusion or surgical ligation of patent ductus arteriosus. The patients were assigned to 2 groups based on their ductal diameter: >/= 3.1 mm to group A (n = 27) and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
50
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 19 publications
14
50
1
Order By: Relevance
“…In accordance with the present study Galal et al [13] reported that closure of a relatively large PDA results in a sudden reduction in LV volume overload, thereby reducing muscle fiber stretch and decreasing systolic function. He hypothesized that changes in after load may be another contributory factor adversely affecting LV systolic performance.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the present study Galal et al [13] reported that closure of a relatively large PDA results in a sudden reduction in LV volume overload, thereby reducing muscle fiber stretch and decreasing systolic function. He hypothesized that changes in after load may be another contributory factor adversely affecting LV systolic performance.…”
Section: Discussionsupporting
confidence: 93%
“…Immediate reduction in preload and an increase in afterload are associated with effective closure of left‐to‐right shunting PDA and result in decreases in left ventricular size (typically diastolic more than systolic dimensions) and left atrial size, as well as a reduction in left ventricular fractional shortening (FS) 3, 4, 5, 6, 7, 8. Within 6 months of PDA closure in human patients, left ventricular size continues to decrease and systolic function often improves, although recovery of systolic function can take longer, particularly in patients presenting for PDA closure as adults 3, 9, 10. Additional factors that affect the degree of left ventricular reverse remodeling (normalization of size and systolic function) include low ejection fraction before PDA closure in human patients, the presence of residual ductal flow after PDA closure in human patients and dogs, and acquired heart disease (HD) in dogs 3, 4, 5, 11.…”
mentioning
confidence: 99%
“…PDA closure is required in patients with signs of LV volume overload, pulmonary arterial hypertension or symptoms of heart failure (3). Transient LV dysfunction following PDA closure has previously been reported, although severe complications are rare (7)(8)(9)(10). The present study reported the case of an adult patient with PDA and bicuspid aortic valve (AV) who experienced transient severe LV dysfunction following percutaneous closure of PDA.…”
Section: Introductionmentioning
confidence: 87%
“…PDA presents with a broad spectrum of clinical manifestations ranging from asymptomatic cardiac murmur to severe complications, including congestive heart failure or Eisenmenger syndrome, which are predominantly associated with the amount of left-to-right shunting and the size of PDA (3,5). Treatment of the majority of PDAs is accomplished by surgical or catheter closure with a complete closure rate of 90-95% (3,(6)(7)(8)(9). PDA closure is required in patients with signs of LV volume overload, pulmonary arterial hypertension or symptoms of heart failure (3).…”
Section: Introductionmentioning
confidence: 99%